Tail conspicuousness and antipredatory behaviour in Bosk's fringe-toed lizard (Acanthodactylus boskianus). Issue 4 (4th July 2018) - Nasri, Intissar; Hamza, Foued; Belliure, Josabel; Selmi, Slaheddine
Abstract : Many lizard species show ontogenetic changes in tail colour that are coupled with changes in the antipredatory strategy. However, the ecological factors that influence the relationships between age, tail colour and antipredatory strategy remain poorly understood. In this work, we investigated how antipredatory behaviours vary according to age in Bosk's fringe-toed lizard ( Acanthodactylus boskianus ), a species that shows ontogenetic changes in tail colour. First, we verified whether tail conspicuousness increases the probability of predatory attacks, by using two types of plasticine models made to mimic juveniles (red-tailed models) and adults (beige-tailed models) and distributed in a study plot where an avian predator is abundant. We found that juvenile-like red tails were more frequently attacked by predators than the less conspicuous adult-like ones. We also conducted predation simulation experiments on active lizards of different ages and compared their risk-taking and escape behaviours. Adults occurred close to potential refuges (i.e. bushes), while juveniles were more commonly observed in open microhabitats. When approached by the observer, adults rarely conducted tail displays and usually fled in a non-stop way to penetrate inside the nearest bush. However, juveniles conducted tail displays and never fled directly inside a bush. They usually stopped near the target bush and tolerated a closer approach from the observer before making the decision to take refuge inside the bush. It seems that juveniles feared the attacks of adults and avoided entering bushes occupied by adults. Repeated observations of adults acting aggressively towards juveniles provide support for this hypothesis. Overall, our findings highlight the role of tail conspicuousness in the diversion of predatory attacks from the vital parts of the body in the juveniles of Bosk's fringe-toed lizard. They also suggest that agonistic interactions between adults and juveniles play important roles in shaping their antipredatory behaviour.